STUDY ON CRACK INITIATION AT GRAIN BOUNDARY OF Cu⁃Ni⁃Si ALLOY BASED ON CRYSTAL PLASTICITY AND COHESIVE ZONE MODEL - TAO Meng; YU PeiShi; ZHAO JunHua (Jixie qiangdu)
The macroscopic failure behavior of metal materials is closely related to the damage evolution of microstructure.In addition to in⁃situ loading experiments,advanced numerical methods are used to simulate and predict the microstructure evolution of metal materials,which has gradually become an effective tool to study the multi⁃scale damage evolution mechanism of metal materials.At present,the dislocation motion inside polycrystalline metal grains can be simulated by crystal plastic finite element method,but there are still challenges in the simulation of damage accumulation and microcrack initiation caused by dislocation.For most metal polycrystalline materials,dislocations are usually plugged at grain boundaries leading to stress concentration and then cracking at grain boundaries.Therefore,the simulation of the whole process requires the construction of a numerical model that can describe both dislocation motion and grain boundary cracking.In order to solve this problem,combining the crystal plastic finite element model with the cohesive zone model to achieve a uniform description of material microscopic deformation and damage,and a global finite element model to describe dislocation motion and grain boundary cracking was established.Then,taking polycrystalline Cu⁃Ni⁃Si alloy as the research object,the microstructure evolution process from deformation,crack initiation,crack propagation to fracture was simulated,and the mechanism from local intergranular fracture to global failure was revealed,and the effect of grain orientation on initial fracture location and crack propagation was clarified.This model provides a feasible methodology for multi⁃scale damage evolution simulation of the failure behavior of various metal materials.